PENGARUH BUDAYA ORGANISASI ISLAMI, KEPEMIMPINAN ISLAMI DAN KOMPETENSI SUMBER DAYA MANUSIA ISLAMI TERHADAP KINERJA PEGAWAI DI MADRASAH TSANAWIYAH NEGERI BARITO SELATAN KABUPATEN BARITO SELATAN: The Effect Of Islamic Organizational Culture, Islamic Leadership And Islamic Human Resources Competency On Employee Performance In Madrasah Tsanawiyah Negeri Barito Selatan in South Barito District - MAHRIDI, MUHAMMAD BUKHARI MUSLIM (Pencerah Publik, 2022)
Employee performance is very important in supporting the operational activities of the agency, so that every head of a government agency is required to be able to improve the performance of its employees. Various efforts can be made to improve employee performance starting from creating an Islamic organizational culture, Islamic leadership and Islamic human resource competencies owned by the agency. This study aims to analyze the influence of Islamic organizational culture, Islamic leadership and Islamic human resource competence on employee performance at Madrasah Tsanawiyah Negeri Barito Selatan. The author uses quantitative research methods, with a sample of 56 people. The sampling technique in this study used saturated sampling and data collection techniques through observation, documentation, questionnaires and interviews and the statistical analysis used was multiple linear regression analysis. The results obtained indicate that the variables of Islamic organizational culture (X1), Islamic leadership (X2) and Islamic human resource competence (X3) together (simultaneously) have a significant effect on employee performance, where Fcount > Ftable is 19,092 > 2,783 (Ho rejected), then together the independent variables also contribute to employee performance by 52.4%. As for the partial variables X1, X2 and X3 have a significant effect on the Y variable with the contribution of each variable’s value of 19.53%, 4.08%, and 28.79%. Based on the conclusion that if individual performance is good, it is likely that organizational performance is also good and an employee’s performance is good if he has high knowledge and skills, is willing to work for a salary or is paid according to the agreement and has high future expectations. better, with strategies, programs, activities and development with an Islamic perspective that has the principles, goals, vision, mission and values.